ANALISIS FAKTOR RISIKO PADA KANKER SERVIKS DI RUMAH SAKIT BADAN PENGUSAHAAN BATAM - Acholder T Perdoman; Ipaljri Saputra, Andi; Yafia Rahmi (Universitas Batam, 2025)
ABSTRACT Background: Cervical cancer is a leading cause of cancer-related death among women worldwide, with a high prevalence, particularly in developing countries. The primary cause of cervical cancer is infection with the human papillomavirus (HPV). Other risk factors include smoking habits, a history of vaginal childbirth, the use of hormonal contraceptives, and age. Methods: The study uses a quantitative approach with an analytical observational design employing Pearson correlation analysis. Data is collected from patient medical records. Results: The research results on 183 samples showed a strong correlation (p=0.000),(r = 0.722) between smoking history and cervical cancer, a moderate correlation (p=0.000),(r = 0.625) between vaginal delivery history and cervical cancer, a very weak correlation (p=0.154),(r = 0.106) between contraceptive use and cervical cancer, and a weak correlation (p=0.000),(r = 0.327) between age and cervical cancer in OB-GYN patients at the Batam Free Trade Zone Hospital in 2023. Conclusion: Based on this research, it is concluded that the null hypothesis (Hᴏ ) is rejected and the alternative hypothesis (Ha) is accepted, meaning there is a correlation between smoking history, vaginal delivery history, contraceptive use, age, and cervical cancer in OB- GYN patients at the Batam Free Trade Zone Hospital in 2023 Keywords: Cervical cancer, Smoking habits, Vaginal childbirth, Hormonal contraceptives, Age